Implementation of National Standards of Education in Higher Education - Hani Hadiati Pujawardani; Miftahussalam Miftahussalam; Nur Sobarie; Muchtarom Muchtarom (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to analyze the implementation of National Education Standards (SNP) in Higher Education by conducting case studies at the Uninus Graduate School. The implementation of SNPT in the context of higher education has an important role to ensure optimal quality of education and meet the needs of stakeholders. The research method used is a qualitative approach with data collection through interviews, observation, and document analysis. The respondents of this study consisted of academic staff, students, and leaders of the Uninus Graduate School. The results showed that the Uninus Graduate School has made significant efforts in implementing SNP in the curriculum and learning process. In implementing SNPT, the Uninus Graduate School has involved qualified and competent lecturers in teaching, developing curricula that are relevant to the demands of the development of science and technology, and providing quality learning experiences for students. In addition, regular monitoring and evaluation of SNPT implementation has also been carried out to ensure conformity with established standards. Nonetheless, the study also identified several obstacles in the implementation of SNPT at the Uninus Graduate School. Some of these obstacles include the need for better resources, such as adequate facilities and infrastructure, as well as continuous curriculum development to remain relevant to the development of science and the needs of the world of work. This research makes an important contribution to the understanding of SNPT implementation in higher education. The results of this research can be a reference for other universities in implementing SNPT, as well as providing recommendations for further improvement and development in an effort to improve the quality of education at the Uninus Graduate School and other universities